The Mako ™ robotic arm-assisted total hip arthroplasty using direct anterior approach: surgical technique, skills and pitfals - Perazzini , Piergiuseppe; Trevisan , Michele; Sembenini, Paolo; Alberton, Francesco; Laterza, Mara; Marangon, Alberto; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2020)
In the last decades many innovations have improved the hip replacement and the hip reconstruction surgery such as the introduction of the robotic-arm assisted surgery associated with the direct anterior approach (DAA). This surgical approach for total hip arthroplasty (THA) is growing in popularity and its effectiveness has been demonstrated to improve patients’ outcomes, especially regarding more accurate implant placement, less post operative pain, faster recovery and lower of prosthesis dislocation risk. The robotic-arm assisted surgery is another really great innovation for the orthopedic surgeons. It allows to create a patient-specific THA pre-operative planning and to perform a much more accurate surgical procedure. This article outlines authors’ surgical technique of performing accurate pre-operative planning and robotic-assisted THA using direct anterior approach based on the experience of 534 patients and to discuss details of this technique.